The development of Bayer derived geopolymers as artificial aggregates - Jamieson, Evan; Penna, B.; Van Riessen, Arie; Nikraz, Hamid (Elsevier, 2015)
© 2016 Elsevier B.V. The Bayer process is the hydrometallurgical production of alumina, subsequently used within the chemicals industry and for smelting to aluminium. Bauxite deposits have with time become more problematic to process, frequently containing impurities that build up within the Bayer process liquor, reducing circuit efficiency and requiring dedicated reduction processes. The Bayer Circuit and residue washing processes are based upon the retention of the costly process liquor resulting in some impurities continuing to concentrate till they reach their solubility limits. A counter intuitive method of impurity removal is the export of a Bayer liquor bleed stream and its replacement with clean caustic. The Bayer liquor bleed stream would need to be of sufficient volume to act as an impurity removal process, but what to do with the costly and highly caustic aluminate solution? Following concentration, the Bayer liquor can be exported for utilisation in the production of Bayer derived geopolymers, a possible new construction material. Only the commercial application of the Bayer process liquor would allow the utilisation of the impurity removal process, potentially benefiting both industries.Bayer liquor and fly ash (a coal combustion product) have been utilised to make a new class of ambient-cured construction geopolymers with compressive strength in excess of 30. MPa. Industrial synergy allows for the production of Bayer derived flyash geopolymer products of very low embodied energy (concrete binder of 0.27. GJ/t) and associated carbon footprint.To establish a Bayer derived geopolymer industry of large enough volume to allow economies of scale, several product markets and applications will be required to generate consistent demand. One such market is to manufacture artificial aggregate from Bayer-derived geopolymer mortars. An artificial aggregate would normally have a high embodied energy however here it has been calculated to be 0.22. GJ/t, similar to other manufactured or recycled aggregates. Production rates could be between 0.1 and 10 million tonnes per annum per alumina refinery, depending upon local economics and refinery operational conditions.